Concomitant Temperature Stress and Immune Activation may Increase Mortality Despite Efficient Clearance of an Intracellular Bacterial Infection in Atlantic Cod - Larsen, Anett K.; Nymo, Ingebjørg H.; Sørensen, Karen K.; Seppola, Marit; Rødven, Rolf; Jiménez de Bagüés, María Pilar; Al Dahouk, Sascha; Godfroid, Jacques (Frontiers in Microbiology, 2018)
The environmental temperature has profound effects on biological systems of marine aquatic organisms and plays a critical role in species distribution and abundance. Particularly during the warmer seasons, variations in habitat temperature may introduce episodes of stressful temperatures which the organisms must adapt to and compensate for to maintain physiological homeostasis. The marine environment is changing and predicted raises in water temperatures will affect numerous marine species. Translocation of pathogens follow migration of species and alternations in physical environmental parameters may have influence upon the virulence of pathogens, as well as the hosts immune responses. While pathogenicity of many true pathogens is expected to increase following climate induced temperature stress, the impact from environmental stressors on the occurrence and severity of opportunistic infections is unknown. Here we describe how thermal stress in the cold-water species Atlantic cod influenced the fish immune responses against an opportunistic intracellular bacterium. Following experimental infection with Brucella pinnipedialis at normal water temperature (6°C) and sub-optimal temperature (15°C), cod cleared the intracellular bacteria more rapidly at the highest temperature. The overall immune response was faster and of higher amplitude at 15°C, however, a significant number of cod died at this temperature despite efficient clearance of infection. An increased growth rate not affected by infection was observed at 15°C, confirming multiple energy demanding processes taking place. Serum chemistry suggested that general homeostasis was influenced by both infection and increased water temperature, highlighting the cumulative stress responses (allostatic load) generated by simultaneous stressors. Our results suggest a trade-off between resistance and tolerance to survive infection at sub-optimal temperatures and raise questions concerning the impact of increased water temperatures on the energetic costs of immune system activation in aquatic ectotherms.